De novo phosphorylation of H2AX by WSTF regulates transcription-coupled homologous recombination repair. Issue 12 (2nd May 2019) - Ji, Jae-Hoon; Min, Sunwoo; Chae, Sunyoung; Ha, Geun-Hyoung; Kim, Yonghyeon; Park, Yeon-Ji; Lee, Chang-Woo; Cho, Hyeseong
Abstract: Histone H2AX undergoes a phosphorylation switch from pTyr142 (H2AX-pY142) to pSer139 (γH2AX) in the DNA damage response (DDR); however, the functional role of H2AX-pY142 remains elusive. Here, we report a new layer of regulation involving transcription-coupled H2AX-pY142 in the DDR. We found that constitutive H2AX-pY142 generated by Williams-Beuren syndrome transcription factor (WSTF) interacts with RNA polymerase II (RNAPII) and is associated with RNAPII-mediated active transcription in proliferating cells. Also, removal of pre-existing H2AX-pY142 by ATM-dependent EYA1/3 phosphatases disrupts this association and requires for transcriptional silencing at transcribed active damage sites. The following recovery of H2AX-pY142 via translocation of WSTF to DNA lesions facilitates transcription-coupled homologous recombination (TC-HR) in the G1 phase, whereby RAD51 loading, but not RPA32, utilizes RNAPII-dependent active RNA transcripts as donor templates. We propose that the WSTF-H2AX-RNAPII axis regulates transcription and TC-HR repair to maintain genome integrity.